Residential Electricity Demand: An Experimental Study - Battalio, Raymond C.; Kagel, John H.; Winkler, Robin C.; Winett, Richard A. (The Review of Economics and Statistics, 1979)
Raymond C. Battalio, John H. Kagel, Robin C. Winkler, Richard A. Winett, Residential Electricity Demand: An Experimental Study, The Review of Economics and Statistics, Vol. 61, No. 2 (May, 1979), pp. 180-189